Analysis of Tourism Potential for Development of Pulau Bidadari, Kepulauan Seribu, DKI Jakarta - Ricky Poda Josua; Rully Besari Budiyanti; Silia Yuslim (Journal of Synergy Landscape, 2022)
Kepulauan Seribu is one of the 10 priority tourist destinations proposed by the Ministry of Tourism of the Republic of Indonesia. This destination can be developed into nature tourism with the concept of marine tourism, ecotourism, and adventure tourism. Bidadari Island is one of the Thousand Islands group which has natural tourism potential in the form of beautiful beaches and historical relics in the form of forts. This study uses qualitative research methods with research instruments in the form of observations to identify existing tourism potential based on 4 important components in tourism, namely attraction, accessibility, amenity, and ancilliary. Based on the identification results, a SWOT analysis was carried out with the aim of further directing the development of Bidadari Island. The results of this study are that the tourism potential on Bidadari Island has the potential to be developed as adventure tourism with several improvements and improvements related to its supporting facilities.